JAROSLAV ERIK FRIČ: UNPRIZED AND UNPRESSED POET - Chrobák, Jakub (Bohemica Olomucensia, 2020)
The aim of the study is to outline the characteristics of the work of J. E. Frič. His work is a significant example of the Moravian Christian underground and combines religious themes and those based on the tradition of "beat generation". Another aim of the study is to remind the importance of the meeting "Price Balance", which allows to professionally analyze and describe those forms of literary work and such personalities that are not in the center of todayʼs research interest. These personalities also represent an essential component of Czech literature.
Keywords: criticism; literature; underground; evaluation; Price Balance; Jaroslav Erik Frič